Early tonsillectomy for severe immunoglobulin A nephropathy significantly reduces proteinuria. Issue 9 (30th September 2020) - Enya, Takuji; Miyazaki, Kohei; Miyazawa, Tomoki; Oshima, Rina; Morimoto, Yuichi; Okada, Mitsuru; Takemura, Tsukasa; Sugimoto, Keisuke
Abstract: Background: Early multiple‐drug therapy for severe childhood immunoglobulin A (IgA) nephropathy prevents the progression of nephritis and improves the long‐term prognosis. Recent studies have focused on the relationship between the pathophysiology of IgA nephropathy and tonsillar focal infection, and the efficacy of tonsillectomy with methylprednisolone pulse therapy in children has been demonstrated. However, no study has reported on the relationship between the period from diagnosis to tonsillectomy and the long‐term prognosis of IgA nephropathy. Methods: To clarify the long‐term effects of an early tonsillectomy, 40 patients who were diagnosed with severe IgA nephropathy in childhood and underwent a tonsillectomy were divided into two groups based on the period from diagnosis to undergoing tonsillectomy: Group A, less than 3 years; and Group B, more than 3 years. The primary endpoint of this study was the change in the amount of proteinuria. Renal prognosis was evaluated 10 years after the diagnosis. Results: This study enrolled 40 patients diagnosed with severe IgA nephropathy in childhood who underwent tonsillectomy after multiple‐drug therapy with/without methylprednisolone pulse therapy at Kindai University Hospital; eight patients were excluded based on the exclusion criteria. Group A consisted of 18 patients and Group B, 14 patients. Proteinuria and hematuria levels were significantly reduced in the early surgery group ( P < 0.01). No significant differences were found in serum creatinine, uric acid, and IgA/C3 ratio. Conclusions: High proteinuria levels worsen the renal prognosis in IgA nephropathy. Tonsillectomy in less than 3 years combined with multiple‐drug therapy after the initial diagnosis could improve long‐term prognosis.